GLOBAL SOFTWARE DEVELOPMENT: A REVIEW OF ITS PRACTICES - Ali, Naveed; Lai, Richard (Malaysian Journal of Computer Science, 2021)
Global Software Development (GSD) is multi-site software development with software teams scattered across different places around the world. To gain the benefits of the lower cost of software development and access to international talents, many organizations are using GSD. However, earlier studies reported that achieving these benefits can be difficult and GSD involves risks. This paper presents a systematic review of GSD and aim to provide the findings about the current practices, benefits, associated risks, and difficulties associated with it.The review was conducted in accordance with the systematic review procedures and processes defined by Kitchenham. By following these guidelines, six digital libraries to gather information on the prevalent trends and practices in GSD were searched. The outcomes presented in this study are based on 204 studies, published in peer-reviewed conferences and journals. Our findings will enable readers to understand the current practices, benefits, risks and difficulties associated with GSD. As a result, they can form realistic expectations before making a decision to engage in GSD or not, and formulate better pre-contract and post-contract planning in order to increase the chances of project success. A merit of this paper as compared to previous survey papers on GSD is that it reports the issues related to cultural diversity, requirements engineering and software architecture.